Is a mid‐level dental provider model acceptable to potential patients?. Issue 5 (5th May 2016) - Phillips, Elizabeth; Shaefer, H. Luke; Aksu, Mert N.; Lapidos, Adrienne
Abstract: Objective: This study aims to assess patient attitudes toward mid‐level dental providers, known as dental therapists (DTs), by surveying those likely to be their patients. The recent adoption of accreditation standards by the Commission on Dental Accreditation has reignited a debate surrounding the state‐by‐state legalization of DTs in the United States; while the dental profession is divided on DTs, it is important to understand how potential patients may view the DT model. Methods: A questionnaire that asks about oral health experience, and comfort with the model of a dually trained dental therapist–hygienist, based on a provided definition, was administered to 600 patients and their waiting room companions at a large urban university‐based dental clinic. Results: Forty percent of respondents indicated they would be comfortable being treated by a DT for all 7 of the procedures referenced, and over 75% were comfortable with each of 5 procedures. Having caps or crowns placed was the only treatment about which respondents were evenly divided. Factors associated with greater odds of comfort with various procedures include being uninsured and being under the age of 65. Uninsured patients were 1.5 to 2 times more likely than privately insured patients to accept a DT. Conclusions: The introduction of mid‐level dental providers is a strategy that those lacking regular care appear on the whole to be comfortable with.